The investigation of photoinitiated polymerization of multifunctional acrylates with TX-BT by Photo-DSC and RT-FTIR - Esen, Duygu Sevinc; Karasu, Feyza; Arsu, Nergis (ELSEVIER SCIENCE SA, 2011)
Photopolymerization of multifunctional acrylates with 3H-5-Thia-1,2,3-triaza-cyclopenta[b]anthracene-10-one (TX-BT) as the one-component photoinitiator was investigated using real-time Fourier transform infrared spectroscopy (RT-FTIR). Photo-differential scanning calorimetric (Photo-DSC) technique was used to study the gelation of trimethylolpropanetriacrylate (TMPTA), P-3038 (epoxydiacrylate (EA) 75% and tripropyleneglycoldiacrylate (TPGDA) 25%) and tripropyleneglycol diacrylate (TPGDA)+ P-3038 in the presence of TX-BT. Photopolymerization reactions were performed under different conditions of initiator concentration and UV light intensity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Thioxanthone derivatives; Photoinitiator; RT-FTIR; UV-curing; Epoxy diacrylate; Photo-DSC; IRRADIATION INTENSITY; METHYL-METHACRYLATE; ACRYLIC RESINS; PHOTOPOLYMERIZATION; KINETICS; GELATION; Chemistry; Materials Science